Method for preparing aluminum nitride ceramic coating on surface of aluminum and aluminum alloy through liquid-state low-temperature plasma electrolytic nitridation

By using liquid low-temperature plasma electrolysis technology on the surface of aluminum and its alloys, nitrogen is generated using the non-aqueous electrolyte system to form an AlN ceramic coating in situ, which solves the problems of high-temperature sintering and non-oxide preparation, and realizes AlN ceramic coating at low temperatures The efficient preparation of the layer has excellent electrical insulation and thermal conductivity, and is suitable for high-power integrated circuit packaging.

CN119287475AActive Publication Date: 2025-01-10HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411452418.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing methods require high temperature sintering, with a sintering temperature as high as 1800°C, and it is difficult to sinter densely, and it is not possible to achieve in-situ preparation of non-oxides.

Method used

Using liquid low-temperature plasma electrolysis on the surface of aluminum and its alloys, a non-aqueous electrolyte system that can produce nitrogen is designed, including ammonium chloride and sodium nitrite. It generates nitrogen by heating, and liquid low-temperature plasma electrolytics in the electrolyte. The AlN ceramic coating is formed.

Benefits of technology

It realizes safe, efficient and environmentally friendly growth of AlN ceramic coating on the surface of aluminum and its alloys safely, efficiently and environmentally friendly at temperatures below 1000°C. It has excellent electrical insulation, corrosion resistance and good thermal conductivity, and is suitable for large-scale Power integrated circuit package.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287475A_ABST
    Figure CN119287475A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an aluminum nitride ceramic coating through liquid-state low-temperature plasma electrolytic nitridation on aluminum and aluminum alloy surfaces, and relates to the field of aluminum and aluminum alloy surface modification. The invention aims to solve the problems that high-temperature sintering is generally needed for preparing the AlN ceramic substrate by the existing method, the sintering temperature is up to 1800 DEG C, and the sintering is difficult to compact. The method comprises the following steps: 1, pretreating the surface of an aluminum or aluminum alloy sample; 2, preparing a non-aqueous electrolyte system capable of generating nitrogen; and 3, heating the non-aqueous electrolyte system, putting the pretreated aluminum or aluminum alloy sample into the electrolyte capable of generating nitrogen, continuously introducing N2 into the electrolyte by taking a stainless steel plate or a stainless steel tank as a cathode and the pretreated aluminum or aluminum alloy sample as an anode, and carrying out liquid low-temperature plasma electrolytic nitridation treatment. The method for preparing the AlN ceramic coating on the surface of the aluminum or the aluminum alloy is safe, efficient, environmentally friendly, easy to operate and high in designability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface modification of aluminum and its alloys, and in particular to a method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys. Background Art

[0002] Aluminum nitride (AlN) has the characteristics of high strength, high volume resistivity, high insulation withstand voltage, thermal expansion coefficient, good matching with silicon, etc. It is widely used in the field of ceramic electronic substrates and packaging materials, and its performance far exceeds that of alumina. At present, the preparation of AlN ceramic substrates usually requires high-temperature sintering, with a sintering temperature of up to 1800°C, and it is difficult to sinter densely. Therefore, it is urgent to find a technology that is simple to operate and can prepare AlN ceramic substrates at low temperatures below 1000°C or even below 100°C. Micro-arc oxidation technology can prepare corresponding oxides on the surface of light alloys at room temperature, but it is difficult to achieve in-situ preparation of non-oxides. Based on this, the present invention provides a method for preparing aluminum nitride ceramic coatings by liquid low-temperature plasma electrolytic nitridation in a non-aqueous electrolyte system, which can grow AlN ceramic coatings in situ on the surface of aluminum alloys, and is expected to become an ideal substrate material for high-power integrated circuit packaging. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that the existing method for preparing AlN ceramic substrates usually requires high-temperature sintering, the sintering temperature is as high as 1800°C, and it is difficult to sinter densely, and provide a method for preparing aluminum nitride ceramic coatings by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys.

[0004] The invention provides a method for preparing an AlN ceramic coating on the surface of aluminum or aluminum alloy, which is safe, efficient, environmentally friendly, easy to operate and highly designable.

[0005] A method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys is specifically completed in the following steps:

[0006] 1. Pre-treating the surface of the aluminum or aluminum alloy sample to obtain the pre-treated aluminum or aluminum alloy sample;

[0007] 2. configuring a non-aqueous electrolyte system capable of generating nitrogen;

[0008] The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride and sodium nitrite;

[0009] 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum or aluminum alloy sample is placed in the electrolyte that can generate nitrogen, a stainless steel plate or a stainless steel cell is used as the cathode, and the pretreated aluminum or aluminum alloy sample is used as the anode, and N2 is continuously introduced into the electrolyte. The surface of the aluminum or aluminum alloy sample in the electrolyte is assisted by N2 to undergo liquid low-temperature plasma electrolytic nitridation treatment, and an AlN ceramic coating is formed in situ, thereby obtaining an aluminum or aluminum alloy sample with an aluminum nitride ceramic coating on the surface.

[0010] Principle of the present invention:

[0011] A special non-aqueous electrolyte system is designed. When the electrolyte temperature is greater than 85°C, a large amount of nitrogen can be formed. The electrical parameters are regulated by applying high voltage and large pulse ratio. Under the action of discharge plasma, aluminum or aluminum alloy reacts with nitrogen to grow AlN ceramic coating in situ. At the same time, nitrogen is passed through the electrolyte to provide a sufficient nitrogen source to fully react with the aluminum substrate and ensure the uniform and complete preparation of the AlN ceramic coating. In addition, the non-aqueous electrolyte system will not cause AlN hydrolysis, ensuring the formation of a uniform and complete ceramic coating on the surface of the aluminum substrate. The prepared uniform and dense AlN ceramic coating has excellent electrical insulation, corrosion resistance and good thermal conductivity, and can be used as a ceramic heat dissipation substrate to replace traditional packaging methods.

[0012] The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys provided by the present invention has the following advantages:

[0013] (1) The present invention designs a non-aqueous electrolyte system that can generate nitrogen. The difference between the system and the conventional electrolyte is that the system includes a non-aqueous electrolyte of saturated ammonium chloride and saturated sodium nitrite, and can generate a non-oxide ceramic coating in situ;

[0014] (2) nitrogen is introduced into the electrolyte system to assist in the preparation of the aluminum nitride ceramic coating, further ensuring that there is sufficient nitrogen to react under liquid low-temperature plasma conditions to form the AlN ceramic coating;

[0015] (3) The aluminum nitride ceramic coating on the surface of aluminum and its alloy prepared by the present invention has high electrical insulation and thermal conductivity, and has potential application prospects in the field of electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A flow chart of preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys of the present invention;

[0017] Figure 2 The non-aqueous electrolyte system capable of generating nitrogen prepared in Example 1, (a) is an electrolyte system at room temperature, and (b) is an electrolyte system heated at 85°C;

[0018] Figure 3 This is a SEM image of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0019] Figure 4 The XRD pattern of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0020] Figure 5 The macroscopic morphology of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0021] Figure 6 The bonding strength of the aluminum nitride ceramic coating on the aluminum surface prepared in Examples 1 to 3;

[0022] Figure 7 The electrical insulation properties of the aluminum nitride ceramic coatings on the aluminum surface prepared in Examples 1 to 3;

[0023] Figure 8 The thermal conductivity properties of the aluminum nitride ceramic coating on the aluminum surface prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0024] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0025] Specific implementation method 1: This implementation method is a method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys, which is specifically completed in the following steps (such as Figure 1 shown):

[0026] 1. Pre-treating the surface of the aluminum or aluminum alloy sample to obtain the pre-treated aluminum or aluminum alloy sample;

[0027] 2. configuring a non-aqueous electrolyte system capable of generating nitrogen;

[0028] The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride and sodium nitrite;

[0029] 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum or aluminum alloy sample is placed in the electrolyte that can generate nitrogen, a stainless steel plate or a stainless steel cell is used as the cathode, and the pretreated aluminum or aluminum alloy sample is used as the anode, and N2 is continuously introduced into the electrolyte. The surface of the aluminum or aluminum alloy sample in the electrolyte is assisted by N2 to undergo liquid low-temperature plasma electrolytic nitridation treatment, and an AlN ceramic coating is formed in situ, thereby obtaining an aluminum or aluminum alloy sample with an aluminum nitride ceramic coating on the surface.

[0030] This embodiment uses a non-aqueous electrolyte system that can produce N2, and with the assistance of N2, achieves a high temperature effect and a substantial pressure gradient in the impact local electric field of strong pulse discharge and plasma discharge. When aluminum and its alloys fully react with N2, an AlN ceramic coating with a porous structure is formed, which is expected to become an ideal substrate material for high-power integrated circuit packaging.

[0031] The AlN ceramic coating on the surface of aluminum or aluminum alloy provided by the present invention forms a high electrical insulation / high thermal conductivity AlN ceramic coating on the surface of aluminum and its alloy substrate in one step by using plasma nitridation technology. According to investigation, the existing technology has not been able to achieve one-step in-situ preparation of AlN ceramic coating on the surface of aluminum alloy. At the same time, the technology can prepare AlN ceramic coating with excellent performance at low cost and under temperature conditions below 100°C, which has great originality and is expected to become an ideal substrate material for high-power integrated circuit packaging.

[0032] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the specific method of pre-treating the surface of the aluminum or aluminum alloy sample in step 1 is: polishing the surface of the aluminum or aluminum alloy sample with 600#, 1000#, and 1200# sandpaper in sequence, and then ultrasonically cleaning with acetone and deionized water in sequence. The other steps are the same as those in specific implementation method 1.

[0033] In this embodiment, the purpose of polishing the surface of the aluminum or aluminum alloy sample with 600#, 1000#, and 1200# sandpaper in sequence is to remove burrs on the surface and corners of the aluminum and its alloy sample, remove foreign matter on the surface, and reduce the roughness of the aluminum and its alloy sample;

[0034] In this embodiment, the ultrasonic cleaning time using acetone is 10 minutes to 20 minutes to remove organic pollutants on the surface of the aluminum and its alloy samples;

[0035] In this embodiment, the ultrasonic cleaning time using deionized water is 20 minutes to 40 minutes to wash away the organic residues on the surface, and then air-dried for later use.

[0036] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the sodium nitrite in step 2 is sodium nitrite crystals. The other steps are the same as those in specific implementation method 1 or 2.

[0037] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the sodium nitrite in step 2 is a saturated sodium nitrite solution. The other steps are the same as those of specific embodiments 1 to 3.

[0038] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the molar ratio of ammonium chloride to sodium nitrite in the non-aqueous electrolyte system capable of generating nitrogen in step 2 is 1:1. The other steps are the same as those in specific embodiments 1 to 4.

[0039] In this embodiment, the non-aqueous electrolyte system is heated to above 85° C. in order to allow ammonium chloride and sodium nitrite to react. The reaction equation is as follows:

[0040] NaNO2+NH4Cl==NH4NO2+NaCl(1);

[0041] NH4NO2=N2↑+2H2(2);

[0042] Nitrogen can be generated in the electrolyte through the above reaction formula, which is beneficial for aluminum or aluminum alloy to react in a nitrogen-rich environment to form an AlN ceramic coating.

[0043] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 3, N2 with a pressure of 0.1 MPa and a purity of 99.99% is continuously introduced into the electrolyte. The other steps are the same as those of specific embodiments 1 to 5.

[0044] In this embodiment, the purpose of introducing 99.99% nitrogen at an atmospheric pressure of 0.1 MPa is to assist in the preparation of the aluminum nitride ceramic coating, ensuring that there is enough nitrogen to react the aluminum substrate under the liquid low-temperature plasma discharge conditions to form the AlN ceramic coating.

[0045] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the parameters of the liquid low-temperature plasma electrolytic nitriding treatment described in step 3 include: the electrolyte temperature is 85°C to 100°C, the pulse voltage is 500V to 900V, and the nitriding treatment time is 10min to 60min. The other steps are the same as those of specific embodiments 1 to 6.

[0046] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the aluminum nitride ceramic coating on the surface of the aluminum or aluminum alloy sample in step 3 is a porous structure and is divided into two layers, the inner layer is a dense layer and the outer layer is a porous layer. The other steps are the same as specific embodiments 1 to 7.

[0047] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the thickness of the aluminum nitride ceramic coating on the surface of the aluminum or aluminum alloy sample in step 3 is 5 μm to 100 μm, and the porosity is 5% to 20%. The other steps are the same as specific embodiments 1 to 8.

[0048] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the aluminum nitride on the surface of the aluminum or aluminum alloy sample in step 3 has excellent mechanical properties (high bonding strength, scratch resistance), high electrical insulation, corrosion resistance and good thermal conductivity, and the electrical insulation is ≥ 2000 V. The other steps are the same as specific embodiments 1 to 9.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1: A method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys, which is specifically completed in the following steps:

[0051] 1. Polish the surface of the pure aluminum sample with 600#, 1000#, and 1200# sandpaper in turn to remove burrs on the surface and corners of the pure aluminum sample, remove surface foreign matter, and reduce the roughness of the aluminum and its alloy samples; then use acetone for ultrasonic cleaning for 20 minutes to remove organic pollutants on the surface of the aluminum and its alloy samples, and finally use deionized water for ultrasonic cleaning for 20 minutes to wash away organic residues on the surface, and air-dry for standby use to obtain the pretreated aluminum sample;

[0052] 2. configuring a non-aqueous electrolyte system capable of generating nitrogen;

[0053] The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride, sodium nitrite and deionized water, wherein the molar ratio of ammonium chloride to sodium nitrite is 1:1, and the sodium nitrite is a saturated solution;

[0054] 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum sample is placed in the electrolyte that can generate nitrogen, the stainless steel pool is used as the cathode, the pretreated aluminum sample is used as the anode, and N2 with a purity of 99.99% at a pressure of 0.1 MPa is continuously introduced into the electrolyte, the surface of the aluminum sample in the electrolyte is assisted by N2, and liquid low-temperature plasma electrolytic nitridation treatment occurs, an AlN ceramic coating is formed in situ, and an aluminum sample with an AlN ceramic coating having a porous structure is obtained;

[0055] The parameters of the liquid low-temperature plasma electrolytic nitriding treatment described in step three include: the electrolyte temperature is 85° C., the pulse voltage is 600 V (constant voltage mode), and the nitriding treatment time is 20 minutes under stirring conditions.

[0056] The prepared coating surface presents a porous structure with a roughness of 1.7 μm, a porosity of about 15%, and a coating thickness of 12 μm.

[0057] Figure 2The non-aqueous electrolyte system capable of generating nitrogen prepared in Example 1, (a) is an electrolyte system at room temperature, and (b) is an electrolyte system heated at 85°C;

[0058] from Figure 2 It can be seen that the electrolyte is light yellow, and after heating it, the color of the electrolyte changes slightly, and a large amount of nitrogen is generated.

[0059] Figure 3 This is a SEM image of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0060] Depend on Figure 3 It can be seen that the coating surface presents a porous structure with a roughness of 1.7 μm, a porosity of about 15%, and a coating thickness of 12 μm.

[0061] Figure 4 The XRD pattern of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0062] Figure 4 The horizontal axis 2Theta represents 2θ, and the vertical axis Intensity represents intensity, which is in arbitrary units and represents relative intensity. Figure 4 It can be seen that the main phase component of the AlN ceramic coating prepared on the pure aluminum surface is AlN phase, indicating that a ceramic coating with AlN as the main phase is formed on the aluminum surface under the induction of liquid low-temperature plasma discharge.

[0063] Figure 5 The macroscopic morphology of the aluminum nitride ceramic coating on the aluminum surface prepared in Example 1;

[0064] from Figure 5 It can be seen that the AlN ceramic coating is evenly prepared on the surface of the aluminum substrate.

[0065] Example 2: A method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys, which is specifically completed in the following steps:

[0066] 1. Polish the surface of the pure aluminum sample with 600#, 1000#, and 1200# sandpaper in turn to remove burrs on the surface and corners of the pure aluminum sample, remove surface foreign matter, and reduce the roughness of the aluminum and its alloy samples; then use acetone for ultrasonic cleaning for 30 minutes to remove organic pollutants on the surface of the aluminum and its alloy samples, and finally use deionized water for ultrasonic cleaning for 30 minutes to wash away organic residues on the surface, and air-dry for standby use to obtain the pretreated aluminum sample;

[0067] 2. configuring a non-aqueous electrolyte system capable of generating nitrogen;

[0068] The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride, sodium nitrite and deionized water, wherein the molar ratio of ammonium chloride to sodium nitrite is 2:1, and the sodium nitrite is a saturated solution;

[0069] 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum sample is placed in the electrolyte that can generate nitrogen, the stainless steel pool is used as the cathode, the pretreated aluminum sample is used as the anode, and N2 with a purity of 99.99% at a pressure of 0.1 MPa is continuously introduced into the electrolyte, the surface of the aluminum sample in the electrolyte is assisted by N2, and liquid low-temperature plasma electrolytic nitridation treatment occurs, an AlN ceramic coating is formed in situ, and an aluminum sample with an AlN ceramic coating having a porous structure is obtained;

[0070] The parameters of the liquid low-temperature plasma electrolytic nitriding treatment described in step three include: the electrolyte temperature is 95° C., the pulse voltage is 700 V (constant voltage mode), and the nitriding treatment time is 30 minutes under stirring conditions.

[0071] The prepared coating surface presents a porous structure with a roughness of 1.8 μm, a porosity of about 16%, and a coating thickness of 26 μm.

[0072] Example 3: A method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys, which is specifically completed in the following steps:

[0073] 1. The surface of the pure aluminum sample was polished with 600#, 1000#, and 1200# sandpaper in turn to remove burrs on the surface and corners of the pure aluminum sample, remove foreign matter on the surface, and reduce the roughness of the aluminum and its alloy samples; then, acetone was used for ultrasonic cleaning for 40 minutes to remove organic pollutants on the surface of the aluminum and its alloy samples, and finally, deionized water was used for ultrasonic cleaning for 40 minutes to wash away organic residues on the surface, and the samples were air-dried for standby use to obtain the pretreated aluminum samples;

[0074] 2. configuring a non-aqueous electrolyte system capable of generating nitrogen;

[0075] The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride, sodium nitrite and deionized water, wherein the molar ratio of ammonium chloride to sodium nitrite is 1:2, and the sodium nitrite is a saturated solution;

[0076] 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum sample is placed in the electrolyte that can generate nitrogen, the stainless steel pool is used as the cathode, the pretreated aluminum sample is used as the anode, and N2 with a purity of 99.99% at a pressure of 0.1 MPa is continuously introduced into the electrolyte, the surface of the aluminum sample in the electrolyte is assisted by N2, and liquid low-temperature plasma electrolytic nitridation treatment occurs, an AlN ceramic coating is formed in situ, and an aluminum sample with an AlN ceramic coating having a porous structure is obtained;

[0077] The parameters of the liquid low-temperature plasma electrolytic nitriding treatment described in step three include: the electrolyte temperature is 100° C., the pulse voltage is 750V (constant voltage mode), and the nitriding treatment time is 40 minutes under stirring conditions.

[0078] The prepared coating surface presents a porous structure with a roughness of 2.5 μm, a porosity of about 30%, and a coating thickness of 46 μm.

[0079] Figure 6 The bonding strength of the aluminum nitride ceramic coating on the aluminum surface prepared in Examples 1 to 3;

[0080] Figure 7 The electrical insulation properties of the aluminum nitride ceramic coatings on the aluminum surface prepared in Examples 1 to 3;

[0081] Figure 8 The thermal conductivity properties of the aluminum nitride ceramic coatings on the aluminum surface prepared in Examples 1 to 3;

[0082] from Figure 6 to Figure 8 It can be seen that:

[0083] The coating prepared in Example 1 has excellent mechanical properties (bonding strength of 42MPa); excellent electrical insulation (breakdown voltage of 552±12V; insulation resistance of 168±9MΩ); high corrosion resistance (neutral salt spray resistance>1500h); good thermal conductivity (179±12W / mK);

[0084] The coating prepared in Example 2 has excellent mechanical properties (bonding strength up to 38MPa); excellent electrical insulation (breakdown voltage up to 1092±34V; insulation resistance up to 199±8MΩ); high corrosion resistance (neutral salt spray resistance>1500h); good thermal conductivity (163±9W / mK);

[0085] The coating prepared in Example 3 has excellent mechanical properties (bonding strength of 35MPa); excellent electrical insulation (breakdown voltage of 1190±29V; insulation resistance of 263MΩ); high corrosion resistance (neutral salt spray resistance>1500h); and good thermal conductivity (154±14W / mK).

Claims

1. A method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys, characterized in that The preparation method is specifically completed according to the following steps:

1. Pre-treating the surface of the aluminum or aluminum alloy sample to obtain the pre-treated aluminum or aluminum alloy sample; 2. configuring a non-aqueous electrolyte system capable of generating nitrogen; The non-aqueous electrolyte system capable of generating nitrogen in step 2 comprises ammonium chloride and sodium nitrite; 3. The non-aqueous electrolyte system is heated to generate nitrogen; the pretreated aluminum or aluminum alloy sample is placed in the electrolyte that can generate nitrogen, a stainless steel plate or a stainless steel cell is used as the cathode, and the pretreated aluminum or aluminum alloy sample is used as the anode, and N2 is continuously introduced into the electrolyte. The surface of the aluminum or aluminum alloy sample in the electrolyte is assisted by N2 to undergo liquid low-temperature plasma electrolytic nitridation treatment, and an AlN ceramic coating is formed in situ, thereby obtaining an aluminum or aluminum alloy sample with an aluminum nitride ceramic coating on the surface.

2. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that In step 1, the specific method for pretreating the surface of the aluminum or aluminum alloy sample is as follows: polishing the surface of the aluminum or aluminum alloy sample with 600#, 1000#, and 1200# sandpaper in sequence, and then ultrasonically cleaning it with acetone and deionized water in sequence.

3. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that The sodium nitrite described in step 2 is sodium nitrite crystals.

4. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that The sodium nitrite described in step 2 is a saturated sodium nitrite solution.

5. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that The molar ratio of ammonium chloride to sodium nitrite in the non-aqueous electrolyte system capable of generating nitrogen in step 2 is (1-2):(1-2).

6. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that In step 3, N2 with a purity of 99.99% at a pressure of 0.1 MPa is continuously introduced into the electrolyte.

7. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that The parameters of the liquid low-temperature plasma electrolytic nitriding treatment described in step three include: the electrolyte temperature is 85°C to 100°C, the pulse voltage is 500V to 900V, and the nitriding treatment time is 10min to 60min.

8. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that In step 3, the aluminum nitride ceramic coating on the surface of the aluminum or aluminum alloy sample is a porous structure and is divided into two layers, the inner layer is a dense layer, and the outer layer is a porous layer.

9. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that In step 3, the thickness of the aluminum nitride ceramic coating on the surface of the aluminum or aluminum alloy sample is 5 μm to 100 μm, and the porosity is 5% to 20%.

10. The method for preparing aluminum nitride ceramic coating by liquid low-temperature plasma electrolytic nitridation on the surface of aluminum and its alloys according to claim 1, characterized in that In step 3, the aluminum nitride on the surface of the aluminum or aluminum alloy sample has excellent electrical insulation, corrosion resistance and good thermal conductivity, and the electrical insulation is ≥2000V.

Citation Information

Patent Citations

  • Method for in-situ generation of aluminum nitride layer on aluminum matrix based on ion nitriding technology

    CN113416916A

  • PROCESS FOR NITRIDING TITANIUM OR ALUMINUM SURFACES AND THEIR ALLOYS

    DD296114A5